The Improvement of Business Efficiency Through Business Process Management - Tatic Kasim; Mahir Haracic; Merima Haracic (Economic Review: Journal of Economics and Business, 2018)
Business Process Management (BPM) represents a constant process in which employees of the BPM department, constantly analyze company's business processes and enhance the same, improve or change them using Business Process Improvement (BPI) and Business Process Reengineering (BPR). The main goal of every company is the maximization of investment. However, other stakeholders of the company have also become increasingly important. Because of this, increasing business efficiency does not only mean cost reduction and profit increase for investors or owners of the company. Under the term increasing business efficiency, we mean the overall increase in the performance of business operations, including those elements that do not have direct connection with company's profit. Besides costs reduction and profits increase, increasing business efficiency includes the increase in the utilization of company resources, improvement of working conditions and customer satisfaction, as well as reduction of the negative impact of company's business on the environment. This study examines the possibility of increasing the efficiency and effectiveness of domestic companies, the improvement of business processes through BPM, BPI, and BPR. The research results point to the conclusion that domestic companies do not have enough knowledge related to this field, that companies do not devote enough attention to BPM, BPI, and BPR, and that there is an opportunity to increase the competitiveness of domestic companies by improving business processes.
Keywords: M10; 330; Business Process Management; Business Efficiency; BPM in BiH companies; continuouslyimprove; Business Process Reengineering; Business Process Improvement